Mean Platelet Volume and Splenomegaly as Useful Markers of Subclinical Activity in Egyptian Children with Familial Mediterranean Fever: A Cross-Sectional Study. (13th July 2015) - Marzouk, Huda; Lotfy, Hala M.; Farag, Yomna; Rashed, L. A.; El-Garf, Kamal
Abstract : Objective . To study whether mean platelet volume (MPV) and splenomegaly could be used as subclinical inflammatory markers in children with familial Mediterranean fever (FMF) at the attack-free period. Patients and Methods . The study included ninety-seven children with FMF. MPV was carried out within 4 hours of blood sampling according to standard laboratory practice. Splenomegaly was determined by abdominal ultrasound (USG). Results . High MPV was detected in 84.45% of our studied patients and was significantly higher in FMF patients with splenomegaly than in patients without splenomegaly. There was a statistically significant correlation between MPV and splenic span (P = 0.045 ). Conclusion . Elevated MPV and its significant correlation with splenic span in FMF children during the attack-free periods support the use of MPV and splenomegaly as useful markers of the subclinical inflammation in FMF patients at the attack-free period.